Cr(VI) reduction in aqueous solutions by using copper smelter slag - Kıyak, Belgin; Özer, Ahmet; Altundoğan, Hamdi Soner; Erdem, Mehmet; Tümen, Fikret (My University, 1999)
The ability of Copper Smelter Slag (CSS) to reduce Cr(VI) in aqueous solutions has been investigated. The extent of reduction is dependent on the amounts of acid and reductant, contact time, Cr(VI) concentration, temperature of the solution and particle size of CSS. The amount of acid is the most important variable affecting the reduction process. When twice the amount of acid required with respect to Cr(VI) was used, Cr(VI) in 100 ml solution (100 mg/l) was completely reduced in a contact period less than 5 min by a 10 g/l dosage of CSS. Reduction efficiency increased with increase in temperature of solution, showing that the process is endothermic. Reduced chromium, and iron and other metals dissolved from CSS were effectively precipitated by using NaOH or calcinated carbonatation sludge from sugar plant.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Copper smelter slag; Carbonatation sludge; Cr(VI) reduction; Chromium removal